Indirect Toll-like receptor 5-mediated activation of conventional dendritic cells promotes the mucosal adjuvant activity of flagellin in the respiratory tract. Issue 29 (26th June 2015) - Fougeron, Delphine; Van Maele, Laurye; Songhet, Pascal; Cayet, Delphine; Hot, David; Van Rooijen, Nico; Mollenkopf, Hans-Joachim; Hardt, Wolf-Dietrich; Benecke, Arndt G.; Sirard, Jean-Claude
Abstract: The Toll-like receptor 5 (TLR5) agonist flagellin is an effective adjuvant for vaccination. Recently, we demonstrated that the adaptive responses stimulated by intranasal administration of flagellin and antigen were linked to TLR5 signaling in the lung epithelium. The present study sought to identify the antigen presenting cells involved in this adjuvant activity. We first found that the lung dendritic cells captured antigen very efficiently in a process independent of TLR5. However, TLR5-mediated signaling specifically enhanced the maturation of lung dendritic cells. Afterward, the number of antigen-bound and activated conventional dendritic cells (both CD11b + and CD103 + ) increased in the mediastinal lymph nodes in contrast to monocyte-derived dendritic cells. These data suggested that flagellin-activated lung conventional dendritic cells migrate to the draining lymph nodes. The lymph node dendritic cells, in particular CD11b + cells, were essential for induction of CD4 T-cell response. Lastly, neutrophils and monocytes were recruited into the lungs by flagellin administration but did not contribute to the adjuvant activity. The functional activation of conventional dendritic cells was independent of direct TLR5 signaling, thereby supporting the contribution of maturation signals produced by flagellin-stimulated airway epithelium. In conclusion, our results demonstrated that indirect TLR5-dependent stimulation of airway conventional dendritic cells is essential to flagellin's mucosal adjuvant activity.